GREEN THEOLOGY IMPLEMENTATION STRENGTHENS ADIWIYATA MADRASAH STUDENTS’ ECOLOGICAL AWARENESS FOR SUSTAINABLE EDUCATION - Septian Nur Ika Trisnawati; Asep Kusmawan; Praptiningsih Praptiningsih; Fauzan Afrizal (JMIE (Journal of Madrasah Ibtidaiyah Education), 2026)
Environmental damage in Indonesia is becoming increasingly concerning, as reflected in the national Environmental Quality Index. This problem is not only ecological in nature but also relates to the low level of ecological awareness among the community, including students. This research aims to examine the relationship and influence of the implementation of Green Theology values on the ecological awareness of students at Madrasah Ibtidaiyah Negeri 1 Sukoharjo, which implements the Adiwiyata program. Green Theology emphasizes the obligation of humans as caliphs on earth, so its integration into education adds a moral and spiritual dimension to environmental learning. The research used a quantitative approach with total sampling of 147 fifth-grade students, using a four-point Likert scale questionnaire, and analyzed it through validity, reliability, normality, linearity, and Spearman's correlation tests. The results showed that the instruments were valid and reliable, the data were normally distributed, and the relationship between variables was non-linear but significant (p < 0.05). These findings confirm that the internalization of Green Theology values can significantly increase students' ecological awareness, contributing theoretically to Islamic-based environmental education and practically to the strengthening of the Adiwiyata program in madrasahs.